NFκB up-regulation of glucose transporter 3 is essential for hyperactive mammalian target of rapamycin-induced aerobic glycolysis and tumor growth. Issue 1 (1st April 2015) - Zha, Xiaojun; Hu, Zhongdong; Ji, Shuang; Jin, Fuquan; Jiang, Keguo; Li, Chunjia; Zhao, Pan; Tu, Zhenzhen; Chen, Xianguo; Di, Lijun; Zhou, Haisheng; Zhang, Hongbing
Highlights TSC1/TSC2 complex is a negative regulator of Glut3. Loss of TSC1/TSC2 complex up-regulates the expression of Glut3 through the activation of mTORC1 signaling. mTORC1 up-regulates Glut3 via the activation of the IKK/NFκB signaling pathway. Attenuation of Glut3 inhibits oncogenic mTOR-mediated glycolysis and tumorigenesis.